Difficulties presented by people with intestinal stoma during self-care: integrative review (Research, Society and Development, 2020)
Objective: to identify the difficulties presented during or management of the bag by colostomized / ileostomized adults outside the home environment. Method: Integrative review. During the search, the descriptors “ostomy” and “self care” were used, as the Boolean operator “AND”, in electronic bases: National Library of Medicine (MEDLINE) via PubMed, LILACS, The Cochrane Library, CINAHL, Scopus and Embase, considering articles published in qualquer language, temporary cut from 2009 to 2020. Results: Foram found 266 studies, use of two inclusion criteria, foram selected 04 articles. Among the difficulties, the following stand out: withdrawal of dates, cleaning of the bag, trimming of the plate, exchange of the bag, the latter being placed in all the studies. Discussion: The difficulties assigned to the selected studies reveal the need to intensify the evaluations and guidance that must be carried out together with the stomata in the pre, trans and postoperative phases. These actions must be preferentially developed by a nurse or stoma therapist. Conclusion: The importance of the specialized nurse educator role for non-self-care success is highlighted.